2008
DOI: 10.1002/humu.20784
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of citrullinemia type I variants by in vitro expression studies

Abstract: Mild citrullinemia is an allelic variant of classical citrullinemia type I also caused by deficiency of the urea cycle enzyme argininosuccinate synthetase (ASS). Affected patients comprise a biochemical but no clinical phenotype. However, there is no reliable parameter allowing conclusions regarding the course of the disorder or its type of manifestation. The aim of this study was to test the importance of varying levels of ASS residual activities for the severity at diagnosis. Bacterial in vitro expression st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 19 publications
7
59
1
2
Order By: Relevance
“…The c.1168G>A (p.G390R) missense ASS1 variant identified in our patient is so far the single most common variant identified in early-onset citrullinemia type I (Kobayashi et al 1990;Häberle et al 2002;Gao et al 2003;Engel et al 2009;Laróvere et al 2009). Homozygosity for this variant is usually associated with undetectable or severely reduced (less than 2%) residual enzymatic activity (Kobayashi et al 1990;Vilaseca et al 2001;Gao et al 2003;Berning et al 2008). Although associated with severe enzymatic deficiency and neonatal-onset hyperammonemia, this genotype does not systematically equate with poor long-term outcome, as demonstrated in our patient.…”
Section: Discussioncontrasting
confidence: 44%
“…The c.1168G>A (p.G390R) missense ASS1 variant identified in our patient is so far the single most common variant identified in early-onset citrullinemia type I (Kobayashi et al 1990;Häberle et al 2002;Gao et al 2003;Engel et al 2009;Laróvere et al 2009). Homozygosity for this variant is usually associated with undetectable or severely reduced (less than 2%) residual enzymatic activity (Kobayashi et al 1990;Vilaseca et al 2001;Gao et al 2003;Berning et al 2008). Although associated with severe enzymatic deficiency and neonatal-onset hyperammonemia, this genotype does not systematically equate with poor long-term outcome, as demonstrated in our patient.…”
Section: Discussioncontrasting
confidence: 44%
“…In vitro expression studies have shown that milder forms of CTLN1 are due to kinetic variants of well-folded ASS1 enzyme. 12,27 The lack of appropriate animal models has precluded a more complete understanding of the pathogenesis and medical management of CTLN1. Although Ass1 knockout mice have been generated, homozygous knockout animals die shortly after birth, and no histopathological data are available for this model.…”
mentioning
confidence: 99%
“…At least 11 cases have been recorded, in which the diagnosis of citrullinaemia type I has come to light during a pregnancy or in the immediate post-partum period (Kurasawa et al 1998;Gao et al 2003;Ito et al 2004;Dimmock et al 2008;Berning et al 2008;Häberle et al 2010). One of these cases is of especial interest, as the patient, who died during the episode of decompensation, was homozygous for a mutation c.325G>A (p. Ala118Thr) which has been recorded in two other cases of pregnancy-related decom- SCADD Short-chain acylCoA dehydrogenase deficiency, PKU phenylketonuria, MGC methylglutaconyl CoA hydratase deficiency, VLCADD very-long-chain acylCoA dehydrogenase deficiency pensation, but is associated with only very slight reduction of enzyme activity, though altered kinetics (Berning et al 2008). Mutations identified in citrullinaemia type I have recently been reviewed (Engel et al 2009).…”
Section: Mild Phenotypes: the Example Of Citrullinaemiamentioning
confidence: 98%